A Novel SUCLA2 Mutation Presenting as a Complex Childhood Movement Disorder. (February 2017) - Garone, Caterina; Gurgel-Giannetti, Juliana; Sanna-Cherchi, Simone; Krishna, Sindu; Naini, Ali; Quinzii, Catarina M.; Hirano, Michio
SUCLA2 defects have been associated with mitochondrial DNA (mtDNA) depletion and the triad of hypotonia, dystonia/Leigh-like syndrome, and deafness. A 9-year-old Brazilian boy of consanguineous parents presented with psychomotor delay, deafness, myopathy, ataxia, and chorea. Despite the prominent movement disorder, brain magnetic resonance imaging (MRI) was normal while 1 H-magnetic resonance spectroscopy (MRS) showed lactate peaks in the cerebral cortex and lateral ventricles. Decreased biochemical activities of mitochondrial respiratory chain enzymes containing mtDNA-encoded subunits and mtDNA depletion were observed in muscle and fibroblasts. A novel homozygous mutation in SUCLA2, the first one in the ligase coenzyme A (CoA) domain of the protein, was identified. Escalating doses of CoQ10 up to 2000 mg daily were associated with improvement of muscle weakness and stabilization of the disease course. The findings indicate the importance of screening for mitochondrial dysfunction in patients with complex movement disorders without brain MRI lesions and further investigation for potential secondary CoQ10 deficiency in patients with SUCLA2 mutations.